2021
DOI: 10.3390/su132111694
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fire Accident Factors on Construction Sites Using Web Crawling and Deep Learning Approach

Abstract: Fire safety on construction sites has been rarely studied because fire accidents have a lower occurrence compared to construction’s “Fatal Four”. Despite the lower occurrence, construction fire accidents tend to have a larger severity of impact. This study aims at using news media data and big data analysis techniques to identify patterns and factors related to fire accidents on construction sites. News reports on various construction accidents covered by news media were first collected through web crawling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The crawler receives a prioritized set of URLs (Uniform Resource Locators) to visit and collects hyperlinks from those pages. It iteratively downloads the content of the web pages until the specified or predefined criteria are met, such as a certain number of pages visited, a particular keyword or phrase found, or a specific amount of time elapsed (Moon et al, 2018;Cho, 2001;Olston and Najork, 2010).…”
Section: Web Crawlermentioning
confidence: 99%
See 2 more Smart Citations
“…The crawler receives a prioritized set of URLs (Uniform Resource Locators) to visit and collects hyperlinks from those pages. It iteratively downloads the content of the web pages until the specified or predefined criteria are met, such as a certain number of pages visited, a particular keyword or phrase found, or a specific amount of time elapsed (Moon et al, 2018;Cho, 2001;Olston and Najork, 2010).…”
Section: Web Crawlermentioning
confidence: 99%
“…The Internet, a globally connected network system that enables worldwide access, provides a wide range of information resources through a diverse collection of private, public, business, academic, and government networks. These resources, including news, articles, research papers, interviews, reports, and official documents, are valuable for gathering country information for an effective risk assessment (Moon et al, 2018;Shin, 2015;Pathirage et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that most of the causes for absence are directly related to the activities of the workers and their recommended way of performing them [10,11]. However, the adoption of complex ergonomic solutions at construction sites requires long times and the involvement of a wide range of different stakeholders [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the rise of the Internet of Things (IoT) devices and wearable technologies provides for a relatively unobtrusive technology that could enhance safety by helping in the monitoring of the workers' activities and their adherence to the recommended ergonomic and risk-avoidance guidelines. In addition, the analysis of abnormal ways of performing activities, such as walking very slowly or around objects, could provide insight on the conditions of the construction site, allowing taking important measures that mitigate safety risks [11].…”
Section: Introductionmentioning
confidence: 99%